"It was always just a sacrifice I was willing to make": Understanding Women's use of vaginal cleansing products in spite of adverse health effects - Amanda Jenkins; Kieran C. O'Doherty (Elsevier, 2022)
Over the counter vaginal hygiene products, such as feminine washes, douches, sprays, personal wipes and powders, represent a growing market in North America. For example, in a recent Canadian cross-national study conducted with 1435 women, almost half of participants (42%) reported using vaginal wipes at least once in their lifetime (Crann et al., 2018). While there is growing popularity in the use of these products, biomedical literature increasingly suggests there are health risks associated with some of these products, including higher susceptibility to bacterial vaginosis and cervical cancer. This is concerning given the marketing of these products as safe and beneficial to women's vaginal health. This study draws on interviews with a subset of 8 women (from a larger sample of 31 women) about their use of vaginal cleansing products. We explore how these women rationalized their use of vaginal cleansing products despite being aware of health risks and/or experiencing adverse effects. Women's rationalization included describing negative side effects of using the products as a trade-off for having a clean vagina, minimizing unpleasant side effects, and wanting to avoid being labelled as having a dirty vagina. We discuss societal expectations for women to meet unrealistic standards of an idealized clean vagina or risk facing negative consequences when they fail to do so. We situate these findings within broader cultural meanings of women's bodies as problematic and show how they are driven in part by representations of desirable vaginas as 'contained' and free of odour and discharge.